Developing 21st Century Creative Writing Competencies through Edupreneurship and Creativepreneurship in Journalism Education - Nufus, Hayatun; Subyantoro, Subyantoro; Mardikantoro, Hari Bakti; Pristiwati, Rahayu (Pandawan, 2026)
This study focuses on the development of creative writing enrichment books that incorporate 21st-century competencies within journalism courses, aligning with the principles of edupreneurship and creativepreneurship. The enrichment books are designed to enhance students' creative writing abilities while equipping them with critical skills such as problem-solving, creativity, communication, and digital literacy key competencies required in the modern media landscape. Employing a Research and Development (R&D) approach, the study implemented the enrichment books across multiple universities. Initial assessments (pre-tests) indicated that students’ creative writing proficiency was at a